ISO 9126 UNTUK PENGUJIAN GAME EDUKASI MEMBUANG SAMPAH BERBASIS ANDROID - Silvia Ratna (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2021)
Games are applications that are familiar to people from all walks of life. Efforts to increase the efficiency of providing applications that contain educational elements require a variety of alternatives and new innovations in programming to be applied as a tool to simplify the learning process. This study aims to create a game design called the game "Throw your trash" by inserting educational elements about how to dispose of garbage in its place and introducing the types of waste. And the sample used is elementary school students, because of their interest in the theoretical learning process, considering that children prefer to play games. The methodology used is starting from system analysis, design and implementation stages, and testing using ISO 9126.The results of this educational game to throw garbage show that the game application based on the aspect obtained a percentage of 95% of the Functionality test and the results of the analysis of usability testing obtained a percentage of 81.89% Kata Kunci: education, games, testing, android, ISO 9126